(untitled) (Ciudades, 2017)
Amid the systemic crisis in which we find ourselves, we have detected vacancy claim systems or unused spaces. This crisis is breeding ground for the emergence of emerging cases of appropriation of vacant space at different scales. In the current context, it is necessary to collect these spontaneous and emerging processes currently constructed social space, proposing alternatives to urban developmentalist model we have produced so far. The study has been made of the appropriations disused vacant spaces in the city of Madrid: the case of La Tabacalera, Ésta es una Plaza and Campo de Cebada.